Evaluation of the useful life of two fruits using a biodegradable packing of yucca (Manihot esculenta) - López, Sayuri (2017)
The objective of the research was to evaluate a biodegradable container from cassava starch to prolong the useful life of two fruits, strawberry (VESCA) and blackberry (Rubus sp.), stored at room temperature and refrigeration. Three factors were evaluated with two levels each (container, temperature and type of fruit). The variable response was the useful life time, for which it was determined: PH, acidity, °Brix, Color (LAB *) and calorific energy. Both fruits, strawberry and blackberry, were kept up to seven days at room temperature and nine days in refrigeration, using the biodegradable container, obtaining times superior to control (without packaging to the environment).